Algal-Mediated Priming Effects on the Ecological Stoichiometry of Leaf Litter Decomposition: A Meta-Analysis - Halvorson, Halvor M.; Francoeur, Steven N.; Findlay, Robert H.; Kuehn, Kevin A. (Frontiers in Earth Science, 2019)
In aquatic settings, periphytic algae exude labile carbon (C) that can significantly suppress or stimulate heterotrophic decomposition of recalcitrant C via priming effects. The magnitude and direction of priming effects may depend on the availability and stoichiometry of nutrients like nitrogen (N) and phosphorus (P), which can constrain algal and heterotrophic activity; in turn, priming may affect heterotrophic acquisition not only of recalcitrant C, but also N and P. In this study, we conducted a meta-analysis of algal-mediated priming across leaf litter decomposition experiments to investigate (1) bottom-up controls on priming intensity by dissolved N and P concentrations, and (2) effects of algal-mediated priming on the fate of litter-periphyton N and P during decomposition. Across a total of nine datasets, we quantified priming intensity and tested algal effects on litter-periphyton C:N, C:P, and N- and P-specific mass loss rates. Algal effect sizes did not significantly differ from zero, indicating weak or inconsistent algal effects on litter-periphyton stoichiometry and nutrient loss. These findings were likely due to wide variation in algal priming intensity across a limited number of experiments, ranging from strongly negative (410% reduced decomposition) to strongly positive (104% increased decomposition). Correlation and response surface analyses showed that priming intensity switched from negative to positive with increasing dissolved inorganic N:P across datasets. Algal effects on litter-periphyton stoichiometry and nutrient loss further co-varied with dissolved N:P across datasets, suggesting algae most strongly influence the stoichiometry of decomposition under imbalanced N:P, when priming is most intense. Our findings from this limited meta-analysis support the need for additional tests of aquatic priming effects, especially across gradients of N and P availability, with consideration of coupled C and nutrient dynamics during priming of organic matter decomposition.